The integration of human and non-human actors to advance healthcare delivery: unpacking the role of actor-network theory, a systematic literature review - Tadhg Ryan; Nuala Ryan; Briga Hynes (BMC, 2024)
Abstract Background There is an increasing public, societal and policy imperative for effective integration of healthcare delivery systems. Central to integration in healthcare is a focus on people-centred health, access, patient empowerment, interprofessional teamwork and collaboration between all healthcare stakeholders - difficult to achieve in current silo-driven bureaucratic health organisations. Therefore, actor-network theory (ANT) offers a theoretical approach to understanding the complexities of healthcare delivery by unpacking the type of actor's interplay between social elements and immaterial objects, their interactions, interdependencies and power dynamics. Aims The first of its type, this systematic review aims to identify, synthesise, and appraise extant literature on the use and application of ANT in healthcare contexts. Methods This systematic review was conducted in accordance with PRISMA guidelines and registered with PROSPERO. The authors generated a search strategy utilising 31 Boolean terms, conducting electronic searches of MEDLINE, CINAHL Complete, SCOPUS, PubMed, APA PsycINFO, Business Source Complete and Academic Search Complete. The studies obtained were evaluated for inclusion based on their alignment with the specified inclusion and exclusion criteria. Studies were independently evaluated by the authors, with all data synthesised using a thematic analysis. Results From an initial 2,533 studies, the systematic review included 103 studies which utilised ANT within a healthcare context. The analysis of the studies identified trends in the application of ANT across healthcare which we categorised into four themes: healthcare delivery systems, technology and data, integrated care, and innovation management. The findings demonstrated variability and fragmentation in the application of ANT, often diverging from its fundamental principles. Conclusions Decluttering the literature suggests three dimensions for understanding the relationships of actors, unidimensional ANT - based on single actors, bi-dimensional ANT, the relationship between two actors and multi-dimensional ANT, where human and non-human actors interact to impact healthcare outcomes. The limited number of studies on the use of ANT for integrated healthcare research highlights both its importance to the topic and the considerable research gap that must be addressed.